DIGITAL TRANSFORMATION AND FIRM PERFORMANCE IN 2025: THE MEDIATING ROLE OF BUSINESS MODEL INNOVATION AND MODERATING EFFECTS OF GENERATIVE AI AND SUSTAINABILITY (ASEAN CONTEXT) - Xiao, Yanli; Idris, Sidah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study aims to explore how digital transformation (DT) translates into firm performance (FP) in 2025, addressing inconsistent empirical findings by emphasizing the mediating role of business model innovation (BMI) and moderating effects of generative AI (GenAI) and sustainability orientation (SO). Drawing on dynamic capability theory, institutional theory, and value co-creation theory, a conceptual framework is developed with internal, industry, and institutional factors as contextual boundaries. BMI acts as a crucial bridge linking DT to FP; GenAI strengthens the DT-BMI relationship, while SO enhances the BMI-FP link. Contextual factors (e.g., regulatory environments, digital intensity) further shape these relationships. Theoretically, it extends DT research by integrating GenAI and sustainability into dynamic capability and institutional perspectives. Practically, it offers insights for ASEAN firms to balance technological adoption with adaptive business models.